2008
DOI: 10.1021/jp803903x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sulfonated Dyes by Polyaniline Emeraldine Salt and Its Kinetics

Abstract: A method for the removal of anionic (sulfonated) dyes from aqueous dye solutions using the chemical interaction of dye molecules with polyaniline is reported. Polyaniline (PANI) emeraldine salt was synthesized by chemical oxidation. Sulfonated dyes undergo chemical interactions with the charged backbone of PANI, leading to significant adsorption of the dyes. This phenomenon of selective adsorption of the dyes by PANI is reported for the first time and promises a green method for removal of sulfonated organics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(186 citation statements)
references
References 25 publications
9
176
0
1
Order By: Relevance
“…염료의 배출과 오염을 개선하기 위하여, 수중으로 부터 염료성분을 제거하기 위한 여러 가지 방안들이 연구되었 는데, 고급산화 [3], 광촉매 [4], 흡착 [5], 막여과 [6]와 응집법 [7] 등이 Table 2에 나타냈다. …”
Section: 서 론unclassified
“…염료의 배출과 오염을 개선하기 위하여, 수중으로 부터 염료성분을 제거하기 위한 여러 가지 방안들이 연구되었 는데, 고급산화 [3], 광촉매 [4], 흡착 [5], 막여과 [6]와 응집법 [7] 등이 Table 2에 나타냈다. …”
Section: 서 론unclassified
“…Currently, there has been growing interest in finding inexpensive and effective adsorbents alternative to expensive activated carbon. Polyaniline (PAN) shows good potential for adsorbing organic anions of acid and direct dyes from the effluents [4,5]. This is due to the fact that PAN contains imine and amine groups which can adsorb anions via electrostatic interactions or through hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The principle is based on the chelating properties attributed to the electron-donating groups (amine and secondary amino groups) on the polyaniline polymers (Kong et al 2011). Mahanta et al (2008) used polyaniline emeraldine salt for the removal of sulfonated dyes. Ai et al (2010) reported that the polyaniline microspheres possess potential efficiency to remove methyl orange from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%